Triple-bottom line consideration in a boardroom: Malaysian evidence - Ahmad, Saidah Hamizah; Ahmad, Jasmine; Hashim, Rugayah (2011)
The notion of Triple Bottom Line (TBL) has become increasingly fashionable in today's environment. It's presence as part of corporate governance principle is common in most Code of Corporate Governance worldwide. Board of directors are the prime governor of a company. Hence, this study attempts to test the impact of different characteristics of board with TBL performance in Malaysia using a relatively new dataset from the Asian Sustainability Rating Index 2009. Using correlation tools, the study found no relationship between board characteristics and TBL performance. Thus, this evidence suggests that alternative control mechanism should be created to steer board's decision to maximise the interest of stakeholders. It may be the case that board's incentive to maximise TBL performance is still lacking as compared to financial performance.